2010
DOI: 10.1016/j.eja.2010.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen efficiency of wheat: Genotypic and environmental variation and prospects for improvement

Abstract: Winter wheat (Triticum aestivum L.) was grown for 4 years in multi-factorial field trials at Rothamsted, southern England. Thirty nine elite commercial cultivars (primarily short-straw) were grown including those released in the UK over a 25-year period, a selection of continental varieties, and three older, tall varieties. Varieties spanned the quality spectrum from 'bread' to 'feed'. The crops were given ammonium nitrate at five rates in the range 0-350 kg-N/ha as a 3-way split. The aim was to quantify the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
275
5
12

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 369 publications
(316 citation statements)
references
References 35 publications
(34 reference statements)
24
275
5
12
Order By: Relevance
“…Additionally, it was observed that genotypes with the lowest values of GPC were the same as those that showed high values of GY. This result corroborates other studies which have also reported negative associations between these traits (Barraclough et al, 2010;Monaghan et al, 2001).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Additionally, it was observed that genotypes with the lowest values of GPC were the same as those that showed high values of GY. This result corroborates other studies which have also reported negative associations between these traits (Barraclough et al, 2010;Monaghan et al, 2001).…”
Section: Resultssupporting
confidence: 93%
“…The N concentration in the total biomass (NCB) ranged from 2.05% to 3.33% (Figure 4a), and agreeing with the reports of Barraclough et al (2010) and Haberle et al (2008) who found values of percentage of N in grains ranging from 1.52 to 2.87%. This trait was not influenced by an environmental component.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations